The influence of internal restrictions on the elastic properties of anisotropic materials - Kowalczyk-Gajewska, K.; Ostrowska-Maciejewska, J. (Archives of Mechanics, 2004)
The influence of internal restrictions on the elastic properties of anisotropic materials described by Hooke's law is discussed. Spectral decomposition of the stiffness tensor and the compliance tensor is applied. Possible types of restrictions imposed on the deformation modes are considered. An algorithm for accounting for these restrictions in a constitutive law that minimizes stiffening of the material is proposed. As examples, the volume-isotropic materials and fiber-reinforced materials are analyzed.